PsycEXTRA Dataset 2007
DOI: 10.1037/e548052012-439
|View full text |Cite
|
Sign up to set email alerts
|

Social identities in physical activity promotion for sedentary women

Abstract: The importance of regular and life long physical activity, both from a physical and medical perspective and from a psychological well-being perspective, is well documented. Also well documented is the reduction, below sufficient levels, in physical activity participation, particularly for populations such as young and mid-life adult women. Physical activity promotion is, thus, of great importance in modern society. In this thesis, my primary aim is to develop ways to enhance the adoption and maintenance of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 159 publications
(357 reference statements)
0
0
1
Order By: Relevance
“…This is clearly demonstrated in our qualitative findings, where a mother indicated her preparedness to give up personal time because she did not want to be seen as 'the nagging wife'. This is somewhat at odds with research that found that although subjective norms had more influence on intention associated with PA than attitude and perceived behavioural control did, intention was not a strong predictor of behaviour in young to mid-life women (Pearson, 2008).…”
Section: Discussioncontrasting
confidence: 54%
“…This is clearly demonstrated in our qualitative findings, where a mother indicated her preparedness to give up personal time because she did not want to be seen as 'the nagging wife'. This is somewhat at odds with research that found that although subjective norms had more influence on intention associated with PA than attitude and perceived behavioural control did, intention was not a strong predictor of behaviour in young to mid-life women (Pearson, 2008).…”
Section: Discussioncontrasting
confidence: 54%